Limnological changes in two shallow lakes from an urban reserve throughout a complete hydrological cycle: proposals for restoration and management - Sinistro, Rodrigo (2013)
We analysed the fluctuations of the limnological variables and phytoplankton structure in two shallow lakes located in an urban ecological reserve from Buenos Aires city (Reserva Costanera Sur) during a complete hydrological cycle. The results of this investigation showed that the changes in the water level strongly affect the limnological variables and the structure of the phytoplankton communities. In both shallow lakes, the water level was inversely correlated with conductivity (p < 0.05). During the rising waters, a progressive colonisation by floating macrophytes was observed affecting the dissolved oxygen concentrations. We analysed the fluctuation of the algal groups and dominant species, evaluating the changes in the structure in the context of the phytoplankton functional groups, and we observed that the water level was one of the main variables explaining the variations in the community. We propose some alternatives for the management and restoration of the shallow lakes of this reserve.